Equation 1:

3x-4y=-24

Equation 2:

X+Y=-1

Equation 2 can also be written as:

X=-1-Y

Lets assume this is equation 3

SO:

Equation 3:

X=-1-Y

Substituting equation 3 into equation 1:

3(-1-y)-4y=-24

Expanding:

-3-3y-4y=-24

Subtracting:

-3-7y=-24

Shifting -3 to the other side:

-7y=-24+3

Subtracting:

-7y=-21

Dividing:

-y=-21/7

Which is:

-y=-3

Canceling the negative signs:

y=3

So y is 3

For X substitute this value of y into equation 3

Hence:

X=-1-Y

X=-1-3

Solving:

X=-4

So X is -4

3x-4y=-24

Equation 2:

X+Y=-1

Equation 2 can also be written as:

X=-1-Y

Lets assume this is equation 3

SO:

Equation 3:

X=-1-Y

Substituting equation 3 into equation 1:

3(-1-y)-4y=-24

Expanding:

-3-3y-4y=-24

Subtracting:

-3-7y=-24

Shifting -3 to the other side:

-7y=-24+3

Subtracting:

-7y=-21

Dividing:

-y=-21/7

Which is:

-y=-3

Canceling the negative signs:

y=3

So y is 3

For X substitute this value of y into equation 3

Hence:

X=-1-Y

X=-1-3

Solving:

X=-4

So X is -4